Oxidation stability of castor oil in solvent extraction - Adam Ali, O. M. (Penerbit UTM Press, 2016)
The present work aims to investigate the oxidation stability of castor oil obtained via three solvents, namely n-hexane, methanol and petroleum ether. Oxidation test was performed at ambient temperature and 120°C, and the oil was characterized according to its viscosity and acid value at different time intervals. Results show that the n-hexane extract is low in acid value, and exhibits good oxidation stability at ambient condition. For all oil extracts, heating at higher temperature accelerates the oxidation, thus increasing the viscosity and acid value. This behaviour is more pronounced for methanol extract. Although methanol and petroleum ether extracts possess high acid value, the latter reveals a better oxidation resistance at longer heating period compared to the former.